ON THE MARGINS: REQUALIFICATION OF THE WATERFRONT OF SÃO PEDRO DA ALDEIA, RIO DE JANEIRO (CIPEEX, 2022)
THE DISCUSSION ABOUT PUBLIC SPACES HAS BEEN GAINING MORE AND MORE STRENGTH WITHIN URBAN PLANNING IN RECENT YEARS, FOR PERFORMING FUNCTIONS AND BENEFITS TO THE PLACE WHERE IT IS INSERTED AND TO SOCIETY. THIS WORK WILL BRIEFLY ADDRESS PUBLIC SPACES AND THE CONSTRUCTION OF IDENTITY, ESPECIALLY THE EDGE OF THE CITY OF SÃO PEDRO DA ALDEIRA, IN THE INTERIOR OF THE STATE OF RIO DE JANEIRO. THEY AIM TO STUDY THE RELATIONSHIP BETWEEN NATURAL LANDSCAPE AND PUBLIC SPACES, EMPHASIZING THE IMPORTANCE OF PRESERVED SPACES FOR MAINTAINING LOCAL CULTURE AND PRESERVING HISTORY. THE PROPOSAL RECOGNIZES WATER, ROADS AND BUILDINGS AS A SET THAT MAKES UP THE PUBLIC ENVIRONMENT AND PLAYS A KEY ROLE IN LIFE IN SOCIETY, IMPLEMENTED BY A PROJECT THAT CONSIDERS THE ROAD AS A PHYSICAL CONNECTOR BETWEEN THE URBAN AND NATURAL ENVIRONMENT. WITH THE WATERFRONT REQUALIFICATION PROCESS, SOCIAL AND ENVIRONMENTAL ISSUES WILL BE ADDRESSED, SO THAT IN ADDITION TO BOOSTING TOURISM, ECONOMY AND LEISURE, IT CAN ALSO OUTLINE GUIDELINES TO RESOLVE ISSUES OF PUBLIC INFRASTRUCTURE AND APPRECIATION OF HISTORIC BUILDINGS.
Keywords: Urban Requalification; Natural Landscape; Public Place; History